The Inherent Context Awareness of Natural User Interfaces: a Case Study on Multitouch Displays - Blažica, Bojan (Informatica, 2014)
In computer science, context-awareness refers to the capability of a computing device to sense, understand and react to contextual information, i.e. information that is not at the centre of an activity but is still relevant for that activity. A computing device does not necessarily interact with humans at a given moment, but when it does, its Context-Awareness has many implications for human-computer interaction. The thesis that this paper surmises looks at Natural User Interfaces from a Context- Awareness perspective.